Flying through the Cuckoo’s Nest: countering the politics of agency in public criminology - Steckle, Rhys E. (Crime, media, culture, 2020)
In this article, we devote ourselves to the task of reconceptualizing agency in the public criminology movement. We develop an imaginative political framework to circumvent the relational tensions currently ensnaring public criminology discourse. Employing the psychoanalytic theory of Slavoj Žižek, we engage the public criminology literature and its agential-activist notion of political engagement to reveal three primary directives dismissive of alternative praxes of resistance: faith in the State and public, hypocrisy eschewal, and legitimacy. By invoking the distinction between these modes of political engagement through the “fictional social realities” depicted in Ken Kesey’s One Flew Over the Cuckoo’s Nest, we provide insights into how public criminologists can overcome concerns occluding other modes of “going public.” With such a move, we believe that public criminology’s capacity to “translate crime scholarship out of the academy” will evolve and become open to the possibility that “doing nothing” is more effective than may first appear.